Development of Raman Imaging System for time-course imaging of single living cells. Issue 1 (2010) - Zoladek, A.; Pascut, F.; Patel, P.; Notingher, I.
Abstract : Development of novel inverted Raman micro-spectrometer with the ability to perform multi-hours spectral measurements on living cells is presented. Our system combines a Confocal Raman Micro-Spectrometer and Fluorescence Microscope with cell incubator enclosure allowing measurement of cells in extended time period. To illustrate the feasibility of this Raman micro-spectroscopy system for in vitro time-course studies of cells we performed an experiment where the same group of cells were scanned with the laser at 2 hours intervals between the scans over 8 hours to build Raman spectral images and ensure that no changes occur due to laser damage or environmental conditions. Cell viability test was performed with fluorescence microscopy on exactly the same cells at the end of the time-course Raman measurements.